2020
DOI: 10.3390/en13215616
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Investigation of a Microchannel Heat Sink Using Secondary Flows in Trapezoidal and Parallel Orientations

Abstract: Thermal performance enhancement in microchannel heat sinks has recently become a challenge due to advancements in modern microelectronics, which demand compatibility with heat sinks able to dissipate ever-increasing amounts of heat. Recent advancements in manufacturing techniques, such as additive manufacturing, have made the modification of the microchannel heat sink geometry possible well beyond the conventional rectangular model to improve the cooling capacity of these devices. One such modification in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The velocity of the flow and the temperature difference vary inversely, the heat transfer being maximized at the edge with greater velocity and at the one with a smaller velocity (by the greater temperature difference), with those effects being mitigated in the central channels, originating an intermedium heat transfer. The heat transfer increased globally in the vertical heat sink, especially in the central channels that present the greatest comparative gain, whichis in agreement with the conclusions reported in [33]. It is in this regard that it was inferred that the development of a uniformly distributed flow will be advantageous, since it will increase the global heat transfer of the heat sink and will likely cover a greater effective area.…”
Section: Effect On Heat Transfersupporting
confidence: 90%
“…The velocity of the flow and the temperature difference vary inversely, the heat transfer being maximized at the edge with greater velocity and at the one with a smaller velocity (by the greater temperature difference), with those effects being mitigated in the central channels, originating an intermedium heat transfer. The heat transfer increased globally in the vertical heat sink, especially in the central channels that present the greatest comparative gain, whichis in agreement with the conclusions reported in [33]. It is in this regard that it was inferred that the development of a uniformly distributed flow will be advantageous, since it will increase the global heat transfer of the heat sink and will likely cover a greater effective area.…”
Section: Effect On Heat Transfersupporting
confidence: 90%
“…Memon et al [46] studied the effect of secondary flow in two different microchannel heat sink designs, as shown in Figure 8d. The results showed that the I-type inlet-outlet configuration performed better than that of the C-type and Z-type.…”
Section: The Author Study Methods Heat Sinks Design Featuresmentioning
confidence: 99%
“…The basic concept for exploiting the geometrical modification is flow disruptions, reducing the thermal interfacial area, or elevating the velocity distribution along the walls of the heat sink [ 15 ]. The following studies have focused on these passive techniques.…”
Section: Introductionmentioning
confidence: 99%